TINJAUAN GENDER DALAM PERENCANAAN ANGGARAN DAERAH: STUDI FENOMENOLOGI PADA PENYUSUNAN APBD KABUPATEN MAJENE - Muhammad Ihsan Ansari; Indra Basir (Fakultas Ekonomi dan Bisnis, Universitas Muhammadiyah Cirebon, 2024)
This study explores the implementation of gender-responsive budgeting in the planning and budgeting process in Majene Regency, West Sulawesi. The main issue addressed is the low participation of women in budget decision-making, leading to inequities in budget allocations that are not responsive to gender needs. The study aims to gain a deeper understanding of how gender perspectives are integrated into the formulation of the Regional Revenue and Expenditure Budget (APBD). The research employs a descriptive qualitative and quantitative approach with a case study methodology, including in-depth interviews and participatory observation. The findings reveal that despite policies promoting gender mainstreaming, implementation faces several challenges, including institutional resistance and a lack of capacity and understanding regarding the importance of gender perspectives. The novelty of this study lies in its in-depth analysis of the barriers and opportunities in implementing gender-responsive budgeting at the local level, along with recommendations for enhancing the effectiveness of these policies to achieve more inclusive and sustainable gender equality.